Japan as fashion: Contemporary reflections on being fashionable - Onohara, Noriko (Acta Orientalia Vilnensia, 2011)
University of HyogoThis paper examines how Japanese contemporary fashion has been accepted globally, especially in the case of London. The popularity of Japanese fashion in the West started in the 19th century with kimono-style dressing gowns, but for the true design influence known as Japan-shock, we had to wait for the appearance of the avantgarde Japanese fashion designers who participated in the Paris collection in the 1970s and 1980s. A new keyword for ‘fashionable Japan’ today is kawaii, the notion of cute. This is intimately linked to street fashion and subculture and has been established and received as part of ‘cool Japan’ through the worldwide popularity of Japanese manga and anime. Moreover, it could be said that Japan is fashionable and the Japanese are thought of as fashionable people, but who is described as fashionable, and by whom? To reflect upon this statement, ‘the Japanese are fashionable’, as ideology, picking up the globally popular Japanese street fashion magazine FRUiTS, I would like to investigate the double meaning of fashion in the present and also what it means to be fashionable.